Reposisi Muballigh: Dari ‘Personal’ Menuju ‘Agent of Change’ - Asep Shodiqin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2012)
The tendency of changes in society and rituals of the dakwah implementation in term of verbal missionary propaganda (bi al-lisan) are getting left behind, which in turn has affected the alienation of community members from religious values. In fact, the essence of religion is a value, rather than a ritual aspect. The alienation community members of religious values is a fundamental problem and must be observed and solved. And similarly, structural, socio-economic and socio-cultural problems. Departing from these issues, the necessary propagation models in the community empowerment model, people centered development and value oriented development. This paper described about how ideally a muballigh have to changed their orientation from personal into a more social.